“Strategi Guru Al-Qur’an Hadist Dalam Peningkatan Kualitas Bacaan Al-Qur’an Siswa di MTsN Model Praya Kabupaten Lombok Tengah (NTB) Tahun Pelajaran 2014/2015.” - Lalu Muhamad Busroni (LPPM Universitas Qamarul Huda Badaruddin, 2019)
This study aims to find out: (1) How the Strategies of the Qur'anic Hadith Teachers in Improving the Quality of Reading of the Qur'anic Students at the Praya Model of Central Lombok District MTsN (NTB), (2) Supporting Factors and Inhibiting Al-Teacher Strategy qur'an of Hadiths in Improving the Quality of Reading of the Al-Qur'an Students at the Praya Model of Central Lombok MTsN (NTB) and (3) Solutions to the Inhibiting Factors of the Qur'anic Teachers of Hadiths in Improving the Quality of Reading of the Qur'an Model Praya MTsN Central Lombok Regency (NTB). This study uses a qualitative research approach. To obtain research data, researchers used data collection techniques, namely observation, interviews and documentation, then the data obtained in the field were analyzed by data analysis. The results of the study showed that: (1) The strategies used by the Al-qur'ah Hadist teachers in improving the quality of reading of Al-quran students at the Model Praya MTsN Central Lombok Regency (NTB). By way of: First, read it first then followed by students, after that appoint volunteers (one person) to lead reading and follow by other students. Second, instructing students to read with Tartil individually in order to liken reading, after being considered sufficiently covering (the field of fasohah, makhrijul surat, and the rules of tajwidnya) then entered into the development of tilawah art. (2) Supporting and inhibiting factors for the Al-qur'ah Hadist Teacher Strategy in Improving the Quality of Reading of Al-quran students. The supporting factors are a harmonious classroom environment, the availability of adequate facilities and infrastructure, the existence of guidance / guidance in the reading of the Qur'an / Tahsinul Qiro'ah, the full support / rhythmic support between parents, teachers, and principals so that it inspires enthusiasm students in following religious activities. While the inhibiting factor is the number of students in the class is too much so that the Qur'anic learning is not optimal, the teacher has difficulty managing the lesson hours (Time Allocation Distribution), There are inhibiting factors from students in participating in Extra-curricular activities (Guided Reading of the Qur'an / Tahsinul Qiro'ah), (3) Solution to the inhibiting factors of the Qur'anic Hadist teacher in improving the quality of the reading of the Qur'anic students is the formation of awareness of students, Students are advised to enter TPQ / TPA institutions in their respective homes . In addition, it can be through IQRO recitation 'which has been taught and implemented by the Teachers in each of the Musholla, Langgar, and mosques in the local area.